Alcohol Use Disorder Is Differently Associated With Psychotic Symptoms According To Underlying Psychiatric Disorders: A General Population Study. (11th October 2019) - Pignon, Baptiste; Sescousse, Guillaume; Amad, Ali; Benradia, Imane; Vaiva, Guillaume; Thomas, Pierre; Geoffroy, Pierre A; Roelandt, Jean-Luc; Rolland, Benjamin
Abstract: Aims: Psychotic symptoms can occur in the general population, and alcohol use disorder (AUD) is an identified vulnerability factor. However, it remains unclear how AUD is associated with psychotic symptoms, depending on the underlying psychiatric condition. We aimed to compare the prevalence of psychotic symptoms among subjects with different types of psychiatric disorders, i.e. unipolar or bipolar disorders, anxiety disorders, psychotic disorders or no psychiatric disorder, depending on whether or not there was an underlying AUD. Methods: In a 38, 694-subject general population study, we compared the likelihood of occurrence of seven types of psychotic symptoms, depending on the AUD status and the underlying psychiatric disorders, after adjustment for age, sex, marital status, education and income levels. Results: In unipolar depression and anxiety disorders, almost all types of psychotic symptoms were found associated with AUD (odds ratios (ORs) between 1.98 and 2.19). In contrast, in bipolar disorder, only auditory hallucinations were associated with AUD (OR = 2.50). In psychotic disorders, only thought broadcasting was more frequent among subjects with AUD (OR = 1.78). Conclusion: Our findings in depression and anxiety disorders are in line with the 'dual diagnosis' concept, which posits that comorbid psychiatric/addictive disorders form distinctive entities that are more frequently associated with non-specific severity factors, here psychotic symptoms. The co-occurrence of AUD in bipolar/psychotic disorders was not associated with a generalized increased occurrence of psychotic symptoms but altered their manifestations with an increased risk of auditory hallucinations for bipolar disorder and thought broadcasting for psychotic disorders.